Kesetaraan Batas Usia Perkawinan di Indonesia dari Perspektif Hukum Islam - Fitri Yanni Dewi Siregar; Jaka Kelana (MAHAKIM Journal of Islamic Family Law, 2021)
The minimum age limitation for marriage for citizens is in principle intended so that those who are getting married are expected to have adequate thinking maturity, mental maturity and physical strength. However, in legal arrangements regarding the age limit of marriage in Indonesia, both regulated in statutory regulations and the Compilation of Islamic Law is still a problem, as is regulated in Article 7 paragraph (1) of Law Number 1 of 1974 concerning Marriage which distinguishes between the age limit of marriage based on gender, that is for men 19 years and for women 16 years. This writing aims to find out about the equality of the age limit of marriage in the perspective of Islamic law based on the analysis of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. This research is a normative juridical legal research conducted by examining library materials or primary legal material. In normative legal research, law is often conceptualized as what is written in statutory regulations (law in books) or law is conceptualized as a rule or norm which is a benchmark for human behavior that is deemed appropriate or appropriate. The research specification used in this study is a descriptive analytical method that is related to the equality of the age limit for marriage in the perspective of Islamic law, then the conclusion is drawn using the deductive method where the regulations related to the minimum age limit of marriage in Law Number 16 of 2019 concerning Amendments to the Law Number 1 of 1974 concerning Marriage, can also be considered good and safe because it has exceeded the age limit of adulthood by Islamic jurists and does not conflict with Indonesian law and human rights.